Seroprevalensi yang Tinggi dan Faktor-Faktor Risiko Toksoplasmosis pada Darah Donor dan Wanita di Bali (HIGH SEROPREVALENCE AND RISK FACTORS OF TOKSOPLASMOSIS AMONG BLOOD DONORS AND WOMEN IN BALI) - Laksemi, Dewa Ayu Agus Sri; Artama, Wayan Tunas; Wijayanti, Mahardika Agus (Jurnal Veteriner, 2013)
Toxoplasmosis is an important public health problem because of its worldwide distribution, economicand social impact due to high sequele that may cause such as mental retardation and blindness in children.The aims of this study were to asses serological prevalence of toxoplasmosis in donors and women in Baliand get an overview of association between risk factors and toxoplasmosis infection, i.e.: comprising catownership, food pattern, occupation related to contact with raw meat and activities related to contact withsoil. Serum samples were collected from donors consecutively, while simple cluster design was used forsampling woman. Data on demographics and risk factors for toxoplasmosis were obtained usingquestionnaire. Serological prevalence of toxoplasmosis in donors was 35,9%, while in women was 63.9%.Serological prevalence of toxoplasmosis  in donors at District Badung was 29,2%, Tabanan 36.8%, Gianyar25.0%, Denpasar 41.1%, Klungkung 25.0%, and Bangli 8.3%. Serological prevalence of toxoplasmosis  inwomen at District Badung was 33.3%, Tabanan 66.5%, Gianyar 82.5%, Denpasar 71.1%, Klungkung 81.5%and Bangli 16.7%. Risk factor that play a role in toxoplasmosis infection were food pattern and occupationrelated to contact with soil. The seroprevalence of toxoplasmosis in voluntary blood donors and child-bearing age is relatively high due to local habbit of Balinese society that consume raw meat called lawarand sate
Keywords: Toxoplasma gondii, rGRA-1, indirect ELISA, IgG, IgM